Epidemiological Prevalence of Phenotypical Resistances and Mobilised Colistin Resistance in Avian Commensal and Pathogenic E. coli from Denmark, France, The Netherlands, and the UK - Andrew Mead; Candice Billon-Lotz; Rikke Olsen; Ben Swift; Pascal Richez; Richard Stabler; Ludovic Pelligand (MDPI AG, 2022)
Colistin has been used for the treatment of non-invasive gastrointestinal infections caused by avian pathogenic E. coli (APEC). The discovery of mobilised colistin resistance (mcr) in E. coli has instigated a One Health approach to minimise colistin use and the spread of resistance. The aim of this study was to compare colistin susceptibility of APECs (collected from Denmark n = 25 and France n = 39) versus commensal E. coli (collected from the Netherlands n = 51 and the UK n = 60), alongside genetic (mcr-1-5) and phenotypic resistance against six other antimicrobial classes (aminoglycosides, cephalosporins, fluoroquinolones, penicillins, sulphonamides/trimethoprim, tetracyclines). Minimum inhibitory concentration (MIC) values were determined using a broth microdilution method (EUCAST guidelines), and phenotypic resistance was determined using disk diffusion. Colistin MIC values of APEC were significantly lower than those for commensals by 1 dilution (p < 0.0001, Anderson-Darling test), and differences in distributions were observed between countries. No isolate carried mcr-1-5. Three phenotypically resistant isolates were identified in 2/62 APEC and 1/111 commensal isolates. Gentamicin or gentamicin-ceftriaxone co-resistance was observed in two of these isolates. This study showed a low prevalence of phenotypic colistin resistance, with no apparent difference in colistin resistance between commensal E. coli strains and APEC strains.